ANALISIS MAKNA LEKSIKAL PADA TIGA LIRIK LAGU KARYA DEWI LESTARI DALAM FILM PERAHU KERTAS - Fauziah, Mita; Zuhry, Audi Alya (Hasta Wiyata, 2024)
This research is titled "Analysis of Lexical Meaning in Three Song Lyrics by Dewi Lestari in the Movie Perahu Kertas." The purpose of this research is to describe the lexical meaning in three song lyrics from the movie Perahu Kertas, namely Perahu Kertas, Tahu Diri, and Langit Amat Indah by Dewi Lestari. This research uses a qualitative descriptive research method. The data in this study are qualitative data in the form of words, phrases, clauses, or sentences in the form of lexical meanings in the three song lyrics from the movie Perahu Kertas. The data source for this research is the discourse of the song lyrics, namely the songs Perahu Kertas, Tahu Diri, and Langit Amat Indah by Dewi Lestari. The data collection technique used is documentation and note-taking. The results of the study found lexical aspects in the three song lyrics as follows: in the song Perahu Kertas, there are 11 instances of epizeuxis repetition, 4 instances of anaphora repetition, 2 instances of epiphora repetition of words, 4 synonyms, and 2 antonyms. Furthermore, in the song Tahu Diri, there are 2 instances of mesodiplosis repetition, 2 instances of anaphora repetition, 6 repetitions, and 4 antonyms. Lastly, in the song Langit Amat Indah, there are 2 instances of anadiplosis repetition, 3 instances of epiphora repetition, 2 instances of epanalepsis repetition, and 2 antonyms.Â